Fintech: Challenges, drivers, and future opportunities - Moccia, Salvatore; Passerini, Katia; Tomic, Igor (Cutter Business Technology Journal, 2019)
This article focuses primarily on the financial services industry, noting the importance of connectivity, digital assets, and regulation. The authors recognize the opportunities and disruptions that fintech creates. They look at how incumbents must respond opportunistically and defensively to fintech adoption.
Keywords: Scopus